Political Ethics According to Al-Farabi's Thought - Yulanda, Atika (Islam Transformatif : Journal of Islamic Studies, 2022)
Politics as it is known to be a fear for some people if misused properly. However, in Al-Farabi's view this is not the case. If politics is used properly it will bring happiness to everyone. He believes that good politics can lead to happiness for everyone and not only certain people. Politics is one of the factors of happiness for humans. in this life, humans cannot escape from the political aspect. politics is a very important part of human life. as contained in the thought of al-Farabi. Happiness in his thinking places politics at the most important place because his part of philosophy has a political goal but politics is not an end in itself but as a means to obtain the ultimate goal for humans. This research is a library research using primary sources from the works of Al-Farabi itself and secondary sources as a supporter of achieving the objectives of this research.Politik sebagaimana yang diketahui, menjadi ketakutan bagi sebagian orang apabila disalahgunakan. Namun, dalam pandangan al-Farabi tidaklah demikian. Jika politik digunakan dengan sebaik-baiknya, maka akan mendatangkan kebahagiaan bagi semua orang. Ia menilai bahwa politik yang baik dapatmengantarkan kepada kebahagiaan bagi semua orang dan bukan saja kepada orang-orang tertentu. Politik menjadi salah satu faktor kebahagiaan bagi manusia. Dalam kehidupan ini, manusia tidak dapat melepaskan diri dari aspek politik. politik menjadi bagian yang sangat penting dalam kehidupan manusia. Sebagaimana yang terdapat dalam pemikiran al-Farabi, kebahagiaan dalam pemikirannya menempatkan politik sebagai tempat yang paling penting karena bagian filsafatnya mempunyai tujuan politik, namun politik bukanlah tujuan dalam dirinya tetapisebagai sarana untuk memperoleh tujuan terakhir bagi manusia. Penelitian ini merupakan penelitian kepustakaan dengan menggunakan sumber primer dari karya-karya al-Farabi dan sumber sekunder sebagai pendukung dari tercapainya tujuan dalam penelitian ini.